The taxonomy of the American Ariadna Audouin (Araneae: Synspermiata: Segestriidae) - Giroti, André Marsola; Brescovit, Antonio Domingos (Zootaxa, 2018)
The spider genus Ariadna Audouin, 1826 currently comprises 102 of 127 described species of Segestriidae. Its distribution comprises all continents (except Antarctica), but it is mostly found on the tropical and subtropical regions. We present a comprehensive taxonomic revision of Ariadna in the American continent, including 2,519 specimens (i.e., type and non-type) from 30 arachnological collections. We present 31 nominal species, among which eight species are new to the science: Ariadna reginae n. sp. from Central America; Ariadna aurea n. sp., Ariadna caparao n. sp., Ariadna gaucha n. sp., Ariadna ipojuca n. sp., Ariadna lemosi n. sp. and Ariadna ubajara n. sp. from Brazil; and Ariadna lalen n. sp. from Chile. Nine species are proposed as junior synonyms: A. pragmatica Chamberlin, 1924 and A. scholastica Chamberlin, 1924 with A. bicolor (Hentz, 1842), A. gracilis Vellard, 1924 and A. conspersa Mello-Leitão, 1941 with A. obscura (Blackwall, 1858), A. murphyi (Chamberlin, 1920) with A. tarsalis Banks, 1902, A. pusilla (Nicolet, 1849) and A. ashantica Strand, 1916 with A. maxima (Nicolet, 1849), A. dubia Mello-Leitão, 1917 with A. boliviana Simon, 1907, and A. spinifera Mello-Leitão, 1947 with A. mollis (Holmberg, 1876). Ariadna comata O. P.-Cambridge, 1898 is revalidated. Two species became nomina dubia: Ariadna solitaria Simon, 1892 and A. tubicola Simon, 1893. The allotype of A. crassipalpa described by Camargo (1950) and the paratype of A. levii described by Grismado (2008), were identified as A. mollis and A. maxima, respectively and have been considered as misidentifications. The male of A. cephalotes and A. comata, and the female of A. calilegua are described for the first time.